2013
DOI: 10.1016/j.shaw.2013.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Dermatoses by Type of Work in Greece

Abstract: BackgroundTo elucidate the relationship between seven occupational dermatoses (ODs) and 20 types of work in Greece.MethodsThis was a prevalence epidemiologic study of certain ODs among 4,000 workers employed in 20 types of enterprise, in 104 companies, in 2006–2012, using data from company medical records, questionnaires, occupational medical, and special examinations. The χ2 test was applied to reveal statistically significant relationships between types of enterprises and occurrence of ODs.ResultsA high perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
27
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 33 publications
5
27
1
2
Order By: Relevance
“…This is the first study to investigate contact urticaria in hairdressing apprentices. A previous study investigating contact urticaria in trained hairdressers reported a prevalence of 16% (24). This is comparable to our findings among apprentices in the fourth year of apprenticeship and recently graduated hairdressers.…”
Section: Discussionsupporting
confidence: 90%
“…This is the first study to investigate contact urticaria in hairdressing apprentices. A previous study investigating contact urticaria in trained hairdressers reported a prevalence of 16% (24). This is comparable to our findings among apprentices in the fourth year of apprenticeship and recently graduated hairdressers.…”
Section: Discussionsupporting
confidence: 90%
“…Although, in our study, the frequency of SD symptoms in hairdressers was found to be 45.1%, this result was not statistically significantly. The prevalence of SD symptoms or hand/forearm eczema symptoms was generally observed to be significantly higher in the hairdresser group, according to the results of some other studies . However, the prevalence of SD symptoms was found to be significantly higher in the car mechanics in this study.…”
Section: Discussionsupporting
confidence: 62%
“…Epidemiological data on contact urticaria in hairdressers are sparse , and the only existing data on its occurrence in hairdressing apprentices derive from our baseline study, in which a prevalence of 7.3% was found . Interestingly, the incidence of urticaria on the hands, wrists or forearms was as high as that of hand eczema in both hairdressing apprentices and population controls.…”
Section: Discussionmentioning
confidence: 81%